Oikistes : studies in constitutions, colonies, and military power in the ancient world, offered in honor of A.J. Graham - Gorman, Vanessa B., 1963-; Robinson, Eric W.; Graham, A. J. (Mnemosyne, Supplements, 2002)
This Festschrift includes a range of essays, mirroring the diverse abilities of the honoree, A. J. Graham, in ancient Greek and Roman constitutional history, military history, and colonization. The articles feature discussions of individual problems in politics, epigraphy, historiography, numismatics, and archaeology, including topics such as the Battle of Actium, the Senatus Consultum de Bacchanalibus, the Spartan constitution, democracy in Camarina, Persian coinage, mercenary soldiers, the origins of both Greek and Roman historical writing, cult practice at Berezan, the Athenian Long Walls, the Peloponnesian War, and various aspects of Greek colonization and Roman provincial policy.